La population totale du Canada depuis 1600 - Hamelin, Louis-Edmond (Cahiers de géographie du Québec, 1965)
An attempt is made to calculate the population of Canada since the period of discovery. The author bas made a few corrections to official statistics and bas added the figures for Newfoundland (prior to 1949) and for the Indians and Eskimos (prior to 1851). Throughout it is a question of the same territory, that of present-day Canada.Visualized in this fashion, the history of the population of Canada falls into jour periods :1. 1600-1710 : The total population declined because the slow increase in European immigrants did not compensate for the decrease in numbers of indigenous peoples ;2. 1710-1775 : The total population grew slowly during this period but, after two centuries of colonisation, Canada remained a land of Indians ;3. In less than a century the total population soared from 300,000 to 3,000,000 ; never would Canada experience an equally long period characterized by such a high rate of demographic expansion. Canada became British ;4. The present century bas seen jour demographic periods ; rapid increase took place during two of these periods : 1896-1914 and since 1942.The alternation of rates of growth emphasizes the sensitivity of the Canadian economy to both external and internal events.